(untitled) (World Bulletin of Public Health, 2026)
This article analyzes the new environmental and social challenges arising from the dependence of renewable energy technologies on rare earth elements. In the process of achieving decarbonization goals, the demand for strategic raw materials such as lithium, cobalt, nickel and rare earth elements is increasing sharply. However, the extraction and processing of these metals has environmentally disastrous consequences and is creating a new imbalance between developing countries located in the mining areas and developed countries, which are the centers of consumption. The study analyzes the material flows of green energy based on the theoretical concepts of "ecologically unequal exchange" and "inter-societal just transition". The article highlights China’s monopoly position in the rare earth metals market, social tragedies associated with cobalt mining in the Congo, and the prospects for the development of processing technologies. The author argues that in order to avoid environmental injustice in the process of implementing a "green economy", the author argues that it is necessary to close the material cycle, introduce geographical diversification and international fair trade mechanisms.